A Hotspot Server and Two Line ISP Load Balance and Failover Using the Mikrotik RB951UI 2HND with PCC Method - Muhammad Khaerudin; Andy Achmad Hendharsetiawan; Asep Rhamdani Mahbub; Tukino; Siti Setiawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
When one connection fails, failover makes sure the connection is always available, and the hotspot server can make it simpler for customers to access the internet with a username and password. The loss of an internet connection, a slow connection, and output that is insufficient for your bandwidth are some common issues with the internet network. Managing hotspot servers is less of a worry for many schools and colleges, as they often just use one ISP (internet service provider) connection. The drawback of employing a single line ISP is that blended learning-based lectures will currently cease to exist if the ISP goes down. Therefore, the Mikrotik RB951Ui can do load balancing, failover, and hotspot server management. When using the Per Connection Classifier (PCC) method, which in this study was successful in overcoming the aforementioned issues, the internet connection became stable because the load was split between the two ISPs, and when the internet at one of the ISPs went down, there were still other connections that backed up. Additionally, there is a wifi hotspot management system that uses a username, password, and bandwidth restrictions for each user.